Planning for Future Leadership: Procedural Rationality, Formalized Succession Processes, and CEO Influence in CEO Succession Planning - Schepker, Donald J.; Nyberg, Anthony J.; Ulrich, Michael D.; Wright, Patrick M. (Academy of Management Journal, 2018)
Despite substantive organizational ramifications, surprisingly little theory explains executive succession planning processes. A firm’s board of directors has the fiduciary responsibility to select CEOs, but, historically, boards have failed to exercise this authority. Increasing focus on corporate governance has prompted directors to become more engaged in organizational management, but boards face significant barriers to gathering and processing information. However, there is a dearth of research examining how boards overcome informational barriers to enhance decision-making effectiveness. Accordingly, the current study integrates procedural rationality in decision-making with research on boards as information-processing groups to explore how and why boards conduct succession planning processes. Procedural rationality results in formalized processes designed to collect essential information about CEO succession candidates; these processes, in turn, lead to a greater quantity and quality of CEO succession candidates. We also illustrate how CEOs can influence the effectiveness of board information gathering and processing. The tests of the theoretically generated hypotheses rely on in-depth qualitative interviews, coupled with unique survey and archival data from 355 firm-year observations of 218 large organizations, collected over three years.